Psychological Distress among Breast Cancer Survivor and Their Spousal Caregiver - Sharma, Abha; Sriyuktasuth, Aurawamon; Phligbua, Warunee; Vongsirimas, Nopporn (Journal of Nepal Health Research Council, 2024)
Background: Cancer journey increases the risk for anxiety and depression not only for the breast cancer survivor but also for the spousal caregiver. The purpose of this study was to determine the relationship between psychological distress among breast cancer survivors and their spousal caregivers.Methods: This study used a cross-sectional design where the baseline data on anxiety and depression of breast cancer survivors and their spousal caregivers (dyads) collected for Randomized Controlled Trial were analyzed. Hospital Anxiety and Depression Scale was used to collect data from 64 breast dyads during June to July 2022.Results: Among breast cancer survivors 37.6% had moderate to severe anxiety while 15.6% of spouses had moderate anxiety. Among breast cancer survivors 35.9% had mild, 15.6% had moderate and 4.5% had severe depression level. Among spouses 18.8% had mild and 7.8% had moderate depression level. The anxiety and depression of dyads were positively correlated. There has been significant direct effect of anxiety of survivor on depression of survivors. Moreover, there is significant direct effect of spouse’ anxiety and survivor’s depression on spouse’s depression while survivor’s anxiety has significant indirect effect on spouse’s depression.Conclusions: There has been significant influence of spouse’s anxiety, survivors’ anxiety and depression on the depression level of the spouse. Thus, early dyadic stress management interventions are warranted.Keywords: Anxiety; breast cancer survivor; depression; Nepal; spousal caregiver.